TRE for athletes - Stepišnik Perdih, T. (International Scientific Congress Slovenian Gymnastics Federation, 2018)
The use of vibration as a means for enhancing athletic performance is well documented. Vibration training is based on an external drive that stimulates the neuromuscular system of a subject through the use of a vibratory platform. However, the human body possesses the inherent ability to self-generate vibrations/tremors. Initiating a self-directed tremoring process is the goal of TRE® (Tension, stress, and trauma Releasing Exercises). TRE method is not known among the athletes in Slovenia. Therefore, the aim of our study was to investigate whether; (1) TRE providers around the world use TRE for athletes; and (2) how they find it beneficial. Our findings suggest that TRE can represent a valuable and effective exercise intervention for enhancing performance in athletes. TRE induced tremors are capable of relaxing physical tension patterns in the body as well as reducing psycho-emotional stress and anxiety. However, to adequately assess the effects of TRE on athletes more research is needed. Keywords: TRE, vibrational training, athletes, sports performance, tremor